Establishment of a human nasal epithelium model of histamine-induced inflammation to assess the activity of fexofenadine as an inverse agonist and its link to clinical benefit - Barbot, Anne; Lheritier-Barrand, Michele; Murrieta-Aguttes, Margarita; Leonetti, Maud; Vernaz, Jimmy; Huang, Song; Constant, Samuel; Boda, Bernadett (Frontiers in Pharmacology, 2024)
Background: Fexofenadine (FEX) is an antihistamine that acts as an inverse agonist against histamine (HIS) receptor 1 (H1R), which mediates the allergic reaction. Inverse agonists may be more potent than neutral antagonists, as they bind the same receptor as the agonist (HIS) but stabilise the inactive form and induce an opposite pharmacological response, suppressing the basal activity of H1R and preventing HIS from binding. This study aims to establish and validate a model of HISinduced inflammation based on fully reconstituted human nasal epithelial tissue, to assess the activity of FEX as an inverse agonist in this model and explore its link to clinical benefit. Methods: The model was developed using nasal MucilAir™ (Epithelix) in vitro epithelium challenged by HIS. Two conditions were assessed in a side-by-side comparison: tissue was exposed to HIS+FEX with/without FEX pre-treatment (1-hour prior to HIS challenge). Tissue functionality, cytotoxicity, H1R gene expression and inflammatory cytokines were assessed.Results: HIS at 100 µM induced significant 3.1-fold and 2.2-fold increases for inflammatory biomarkers interleukin(IL)-8 and IL-6 respectively (p<0.0001), and rapid upregulation of H1R mRNA. Inflammatory biomarkers were inhibited by FEX and H1R expression was significantly reduced (p<0.0001). FEX alone decreased H1R expression at all doses tested. With one-hour FEX pre-treatment, there was significantly higher downregulation of IL-8 (p<0.05) and further downregulation of H1R expression and IL-6 versus without FEX pre-treatment; the effects of FEX were improved from 22-40%.Conclusions: A model of HIS-induced airway inflammation was established based on IL-8, IL-6 and H1R gene expression, and was validated with FEX. FEX works as an inverse agonist, with higher effect when used before+during versus just during HIS challenge. Taking FEX before+during allergen exposure, or when symptoms first occur, may reduce basal activity and H1R gene Internal expression, providing stronger protection against the worsening of symptoms upon allergen exposure.